Reducing food waste and promoting sustainable consumption: the role of message framing and controllability attributions in ugly produce marketing - Xiao, Meizhen; Razzaq, Amar; Qing, Ping; Phromphithakkul, Wasin; Thinakaran, Rajermani; Alnafissa, Mohamad (Frontiers in Sustainable Food Systems, 2024)
Food waste due to consumer rejection of aesthetically imperfect produce poses significant challenges to food security and environmental sustainability.The widespread rejection of ugly produce by consumers is a significant contributor to food waste, posing food security and environmental challenges. We construct a matching model between the marketing message framing of ugly produce and the controllability attributions of ugly appearance to drive consumers' purchase intentions. Through theoretical deduction and randomized scenario experiments, we validate this model by demonstrating that consumers' purchase intentions increase when the gainframed (vs. loss-framed) messages for marketing ugly produce match with the high-level (vs. lowlevel) controllability attributions of ugly appearance. In addition, we introduce the concept of consumers' perceived information processing fluency as a mediator in this relationship. The findings provide actionable insights for produce retailers, suggesting that effective and costefficient marketing strategies could reduce food waste and its associated environmental impacts by driving consumers' purchasing intentions to ugly produce, contributing to the achievement of Sustainable Development Goal 2 (SDG 2) and promoting sustainable food systems.